New classification of geometric patterns considering left ventricular volume in patients with chronic aortic valve regurgitation: Prevalence and association with adverse cardiovascular outcomes. Issue 1 (8th November 2018) - Barbieri, Andrea; Giubertoni, Elisa; Bartolacelli, Ylenia; Bursi, Francesca; Manicardi, Marcella; Boriani, Giuseppe
Abstract : Background: Left ventricular (LV) remodeling due to aortic regurgitation (AR) often leads to maladaptive responses. We assessed the prevalence and clinical implications of LV remodeling considering LV volume, mass, and relative wall thickness at the time of AR diagnosis. Methods and Results: Between 2008 and 2017, 370 consecutive patients (mean age 67.3 ± 16.1 years, 56.5% males), with moderate or severe AR, were retrospectively analyzed. LV geometric patterns and clinical outcomes (cardiovascular death, hospitalization for heart failure, or aortic valve replacement) were evaluated. LV dilatation (LV end‐diastolic volume >75 mL/m 2 ) was present in 228 patients (61.6%). Applying the new LV remodeling classification system, 40 (10.8%) patients had normal geometry, 14 (3.8%) concentric remodeling, 43 (11.6%) concentric hypertrophy (LVH), 45 (12.2%) indeterminate LVH, 38 (10.3%) mixed LVH, 93 (25.1%) dilated LVH, 54 (14.6%) eccentric LVH, and 43 (11.6%) eccentric remodeling. During a median follow‐up of 3.48 years (25th–75th percentile 0.91–5.57), 97 (26.2%) had the combined endpoint. LV dilation ( P < 0.001), LVH ( P < 0.001), and LV remodeling patterns were significantly associated with the combined endpoint. After multivariable adjustment for age, EF, aortic stenosis, CAD history, and moderate mitral regurgitation, dilated LVH (HR 7.61, IC 95% 1.82–31.80; P = 0.005) and eccentric LVH (HR 7.91, IC 95% 1.82–34.38; P = 0.006) were associated with adverse outcome compared to eccentric remodeling, that showed the best event‐free survival rate. Conclusions: In a contemporary cohort of patients with AR, applying the new LV remodeling classification system, only a minority had normal geometry. Dilated LVH and eccentric LVH showed distinct outcome penalty after adjustment for confounders.